Coaching journeys: longitudinal experiences from professional football in Great Britain - Watts, D. W.; Cushion, C. J. (Sports Coaching Review, 2017)
The aim of this research was to consider the coaching journeys of eight experienced professional football coaches. In-depth semi-structured interviews were conducted over two data points, a decade apart, and analysed thematically. Findings explored the coaches` longitudinal professional playing and coaching experiences, including their learning and development and engagement with formal coach education over four decades. The coaches` narratives highlighted how their biographies had shaped their identities, learning and practice. Each coach emphasised the importance of experiential learning, learning from other coaches, practicing in diverse coaching domains and the ongoing nature of learning. Data highlighted limitations in formal decontextualised coach education and "fast-tracking". Findings also illustrated something of the changing nature and demands of coaching and how the coaches have adjusted their practice in order to meet the contemporary demands and expectations of their athletes. The coaches reported they required greater education and support around this area. Coaches` journeys are an under-utilised resource and have implications for future coaching practice, coach learning and coach education development.